Immigration: Economic Implications - Sonoma State University Library (Sonoma State University)
SSU Professor Chong-Uk Kim, Santa Rosa Junior College Professor Marty Bennett, and a representative from the Graton Day Labor Center help unravel some of the economics surrounding immigration from a macro and micro perspective.